Numerical simulation of blood flow inside an artery under applying constant heat flux using Newtonian and non-Newtonian approaches for biomedical engineering. (July 2020) - Foong, Loke Kok; Shirani, Nima; Toghraie, Davood; Zarringhalam, Majid; Afrand, Masoud
Highlights: Newtonian and non-Newtonian behaviors of blood flow are simulated. Different parameters of Sisko model are employed. Results of temperature and Nusselt number of blood flow are reported. Effects of different artery radiuses are studied on the Nusselt number. Abstract: Background and objective: In this paper, different behaviors of blood flow are simulated inside the artery under applying a constant heat flux on the artery boundary walls. Methods: To simulate the blood flow, the Sisko model is employed. Then, the temperature and Nusselt number of blood flow are reported for different Sisko parameters. Afterward, the effects of different artery radiuses are studied on the Nusselt number. Results: Medical treatment by replenishes fluid and electrolytes in the body vessels can change blood flow properties from non-Newtonian behavior to Newtonian behavior, which increases heat transfer in blood flow and causes to reduce blood flow temperature. In this research, the maximum temperature of Newtonian blood fluid flow is reported as much as 310.0045 K, whereas; maximum flow temperature in non-Newtonian blood fluid is 310.007 K. These results emphasize the effects of the type of Newtonian and non-Newtonian fluid model on the thermal behavior of blood inside body vessels. Since medical science does not permit body temperature to be changed from the normal condition, this small variation can be noticeable and sensible on the health. Hence, medical scientific research centers and institutes of vaccine and serum have to be careful in the mechanical design of drugs for blood fluid. Conclusions: The results of this research show the application of mechanical engineering for some of the medical concerns in designing the drugs which are effective on the behavior of human body blood.